2012
DOI: 10.3892/etm.2012.648
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of the cyclin D1 G870A variation with oral carcinoma risk: Evidence from 2,404 subjects

Abstract: Evidence implicates cyclin D1 (CCND1) G870A polymorphisms as risk factors for various cancers. An increasing number of investigations have been conducted on the association of CCND1 G870A polymorphisms with susceptibility to oral carcinoma, and have yielded inconclusive results. The aim of the present study was to derive a more precise estimation of the correlation. Meta-analyses examining the association between CCND1 G870A polymorphisms and oral carcinoma were performed. Separate analyses on ethnicity, smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Analogous to these results, Dancau et al found no correlation between survival and CCND1 or PPFIA1/ CCND1 amplification in breast cancer patients (Dancau et al, 2010). The molecular role of PPFIA1 and CCND1 regarding its expression behaviour are still subjects of research (Zhuo et al, 2012). The influence of the PPFIA1 amplification on the PPFIA1 expression could not be examined in this study due to lack of adequate antibodies.…”
Section: Discussionmentioning
confidence: 59%
“…Analogous to these results, Dancau et al found no correlation between survival and CCND1 or PPFIA1/ CCND1 amplification in breast cancer patients (Dancau et al, 2010). The molecular role of PPFIA1 and CCND1 regarding its expression behaviour are still subjects of research (Zhuo et al, 2012). The influence of the PPFIA1 amplification on the PPFIA1 expression could not be examined in this study due to lack of adequate antibodies.…”
Section: Discussionmentioning
confidence: 59%
“…However, the results remain inconsistent and controversial, partially due to the relatively small sample size of independent studies and sampling effects. Meta-analysis allow stronger conclusions for identifying certain models of risk markers, which may aid in screening, early diagnosis and/or therapy in the clinic (19,20). To the best of our knowledge, no previous meta-analysis has focused on the XPA A23G polymorphism and HNSCC risk.…”
Section: Introductionmentioning
confidence: 99%